2017
DOI: 10.4102/sajems.v20i1.1307
|View full text |Cite
|
Sign up to set email alerts
|

Firm characteristics and excellence in integrated reporting

Abstract: Background: Integrated reporting has attracted much attention in the past few years, and South Africa has taken the lead in its development worldwide. An annual survey is published by Ernst & Young regarding the quality of the integrated reports of the top 100 entities listed on the Johannesburg Stock Exchange (JSE).Aim: The study on which this article is based was aimed at determining whether the assessment of an entity’s characteristics can predetermine the quality of the integrated report generated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 20 publications
(21 reference statements)
9
69
1
2
Order By: Relevance
“…Similarly, in a recent research study on integrated reporting, it was found that the majority of integrated reporters are from Europe [52]. In South Africa, perhaps also due to the requirement for IR at the JSE, it was found that companies are more likely to produce an integrated report than in other countries [33,38,43]. For South African organizations, since the introduction of integrated reporting, the disclosure of social and relationship, human, natural, and intellectual capital has increased significantly for listed companies [41].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, in a recent research study on integrated reporting, it was found that the majority of integrated reporters are from Europe [52]. In South Africa, perhaps also due to the requirement for IR at the JSE, it was found that companies are more likely to produce an integrated report than in other countries [33,38,43]. For South African organizations, since the introduction of integrated reporting, the disclosure of social and relationship, human, natural, and intellectual capital has increased significantly for listed companies [41].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 85%
“…Many of the previous studies on voluntary information disclosure have focused on various kinds of voluntary information disclosure such as sustainability reporting or environmental reporting. Some looked into determinants of voluntary disclosure in particular countries or regions [26][27][28][29][30][31][32][33]. Others examined the relationship between certain characteristics in connection with voluntary information disclosure [34][35][36][37].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…This is different from the studies in the literature, which suffer from the following flaws. Firstly, they either used third party assessments of integrated reporting (Buitendag, Fortuin, & De Laan, 2017; Du Toit, 2017). Secondly, they merely assessed the companies' performance without using the mandatory introduction of integrated reporting as an exogenous shock to the company's financial performance (Baboukardos & Rimmel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Corporate value and reputation can be affected by corporate reporting (Hrasky & Smith, 2008), therefore information beyond the financial statements is required for stakeholders to accurately gauge how companies are creating or destroying value (Buitendag et al, 2017;De Villiers & Sharma, 2017;De Villiers & van Staden, 2010b;Flower, 2015;Krzus, 2011b;Phillips et al, 2011;Rahman, 2014;Setia et al, 2015;Wee et al, 2016;Zhou, Simnett, & Green, 2017). Roberts (2011) claims that a focus on the interests and expectations of all stakeholders is bound to be in the best interest of the company as a whole.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the key characteristics of a good report is its ability to convey the necessary information to its wide audience in a way that is easy to read and understand and is appropriate for decision-making (Buitendag, Fortuin, & de Laan, 2017;Chatterjee, 2008;Cook & Sutton, 1995;Eugene Baker III & Kare, 1992;Jones, 1988;Pashalian & Crissy, 1952;Rahman, 2014;Richards & van Staden, 2015). Unfortunately, many studies have found that financial reports are lacking in readability (Anderson, 1998;Bartlett & Chandler, 1997;Hrasky & Smith, 2008;Schroeder & Gibson, 1992), in part as a result of increasing complexity (Eccles & Saltzman, necessarily read corporate reports nor find them useful, which could be a function of reports being difficult to read.…”
Section: [Integrated R]eporting Provides Insight Into How a Company Vmentioning
confidence: 99%